Microcapsule preparation process research and current status of oilfield application - Sicai Wang; Qun Zhang; Jianlong Xiu; Yuandong Ma; Lixin Huang; Lina Yi; Haowei Fu (Micro & Nano Letters)
Abstract Traditional tertiary oil recovery methods are fraught with challenges such as significant reagent adsorption, voluminous injection requirements, limited sweep efficiency, and inadequate intelligent targeting. These issues lead to suboptimal displacement of residual oil, resulting in the inability to mobilize substantial crude oil resources and thus yielding low recovery rates. Microcapsules—spherical particles with micron or nanometer scale diameters—have been extensively utilized across various sectors, including food storage, targeted drug encapsulation, and fragrance containment, owing to their distinct advantages in controlled release, isolation, and targeted delivery. These applications have successfully achieved industrialization and commercialization. In recent years, numerous researchers have explored the application of microcapsule preparation processes to diverse facets of oil extraction, with the aim of further enhancing oil recovery (EOR). This article elucidates the mechanism of action of microcapsules, their preparation methods (encompassing in situ polymerization, interfacial polymerization, spray drying, solvent evaporation, phase separation, and supercritical CO2‐assisted techniques), characterization and evaluation methodologies, among other aspects. It encapsulates the current status and principal challenges associated with the application of microcapsule preparation processes in oilfield development and probes the potential and pivotal research directions for their oilfield applications.